Islamic scholars in Higher Education: A Study of Special Education Programs - Syafaruddin, Baso; Hasbi, Muhammad; Sarda, Muh (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
It is essential for governments and educational institutions, particularly Islamic religious universities, to have a responsibility to guide the community toward understanding Islam as a moderate religion. Thus, this study aims to describe how special education programs are implemented and the competencies of graduates in religious studies at universities that contribute to the development of Islamic scholars. This research is of a descriptive qualitative nature. The subjects of this study consisted of the local government, the rector, the dean, the vice dean, and the head of the study program at As'adiyah Sengkang Islamic University. The data collection techniques employed in this research included observation, interviews, and documentation. The research findings indicate that the implementation of special education programs in the field of religion is equipped with a curriculum, educators who have scientific qualifications, and adequate facilities, infrastructure, and other Islamic insights. Meanwhile, the competencies required for graduates to realize the Islamic scholars include the ability to use Arabic, read classic books, and understand aqidah, sharia, morals, Sufism, da'wah, interpretation of the Qur'an, hadith, and al-urf. The implication of this research is that the program serves as a platform for the government to address and provide solutions to the religious problems faced by society in general.